A peer-to-peer service approach in academic libraries. Issue 3 (3rd July 2021) - Venner, Mary Ann; Washburn, Jenn
Abstract: The role of the student worker is expanding in academic libraries. Their unique perspectives add valuable insights to the design and delivery of library services, project development, outreach activities, and operational planning. Student-workers gain internal and external benefits from working in peer-to-peer learning environments which also inform library managers of ways to improve library operations. The peer-to-peer service model is a framework that library managers can use to facilitate peer-to-peer learning. Lessons learned in expanding the role of the student worker through a peer-to-peer service model are shared and should be considered when creating experiential and operational support for library services.